Effect of Carrageenan as Gelling Agent on Tocopherol Acetate Emulgels - Meiti Rosmiati; Marline Abdassah; Anis Yohana Chaerunisaa (Indonesian Journal of Pharmaceutical Science and Technology, 2018)
Vitamin E (Tocopherol acetate) is used in both oral and topical dosage. The aim of the research was to study different concentration of Carrageenan, as gelling agent in Tocopherol acetate Emulgels. This experimental study was initiated by emulgel formulation using different concentration of carrageenan as gelling agent, as much as 0,5% (F1), 0,75% (F2), 0,85% (F3), 0,95 % (F4), 1% (F5), 1,125% (F6), 1,25% (F7), 1,5% (F8) and 2% (F9). Tween 20 and Span 20 were used as emulsifiers (1 and 1,5 %), Liquid paraffin as oily phase (7,5%), Propylen glycol as humectant (10%), propyl and methyl paraben as antimicrobial preservative (0,01% and 0,03%). The physical investigation of emulgel were included pH, spreading test, viscosity and freeze thawtest. The results for promising formula F5 showed that physical parameters of emulgels were in the range of requirement for topical dosage form. Keywords: Tocopherol acetate (Vitamin E), emulgels, carrageenan